Bond Strength of Nanocomposite Hard Liner to CAD-CAM Milled, 3D Printed, and Conventionally Fabricated Denture Base Resins - Zainab Albazroun; Atheer Alabdullatif; Sarah Aldehaileb; Ferdoos Alhalimi; Faris A. Alshahrani; Soban Q. Khan; Shaimaa M. Fouda; Hamad S. AlRumaih; Mohammed M. Gad (MDPI AG, 2024)
Background: To investigate the effect of zirconium dioxide nanoparticles (ZrO2NPs) on the shear bond strength (SBS) of hard denture lines bonded to different denture base resins. Methods: Five different denture bases were used in this study: conventional heat-cured resin, IvoCad, AvaDent, NextDent, and FormLabs, in acrylic specimens of 10 × 10 × 2.5 mm3 (N = 150, n = 10). Specimens were centered at the bottom of a silicon mold to create an auto-polymerized holder. Three major groups of reline material were used: no ZrO2NPs (control), 2 wt.%, and 4 wt.% ZrO2NPs. Reline was bonded to the resin surface using a customized jig. After polymerization, specimens were stored in distilled water, and 5000 thermal cycles were performed. Each specimen was fixed to an Instron machine, and SBS was tested using a blade loaded (1 mm/min) at the resin interface until failure. Data was collected and analyzed using two-way ANOVA and post hoc Tukey test (α = 0.05). Results: AvaDent showed the highest SBS when compared with other denture base materials (p < 0.001) except for IvoCad. The addition of ZrO2NPs significantly decreased the SBS of AvaDent (p = 0.003) and IvoCad (p = 0.001), while heat polymerized resin, Formlabs, and NextDent showed no significant change in SBS (p > 0.05). Conclusion: CAD-CAM milled denture base resin showed higher SBS with pure denture reline. The addition of ZrO2NPs decreased the SBS of reline with CAD-CAM milled denture base resins but did not change bond strength with 3D printed and conventional denture base resins.